2009
DOI: 10.5694/j.1326-5377.2009.tb03305.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for hepatitis C virus infection in methadone‐maintained mothers and their infants

Abstract: Objective: To describe the patterns of screening for hepatitis C virus (HCV) infection in methadone‐maintained pregnant women and their infants. Design, setting and patients: Retrospective review of medical records from one rural and two metropolitan hospitals in New South Wales for pregnant women on methadone maintenance treatment and infants born to these women between 1 January 2000 and 31 December 2006, as well as records for pregnant women who were not on methadone treatment. Main outcome measures: Rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 17 publications
2
20
1
Order By: Relevance
“…Until recently (2016), HCV infected pregnant in the Milagro Clinic did not get systematic referrals for HCV treatment during postpartum care unless they were abstinent, which may have also contributed to low genotype testing. Overall, the proportion tested, exposed, and infected with HCV in this cohort is similar to that seen in other studies of women with a history of opioid use disorder (Krans et al, 2016; Liu et al, 2009). A recent study of 791 pregnant women with a history of opioid use disorder in Pittsburgh found that a lower proportion were tested (77%) but showed similar anti-HCV prevalence (60.4%) and even lower rates of RNA and genotype testing (Krans et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Until recently (2016), HCV infected pregnant in the Milagro Clinic did not get systematic referrals for HCV treatment during postpartum care unless they were abstinent, which may have also contributed to low genotype testing. Overall, the proportion tested, exposed, and infected with HCV in this cohort is similar to that seen in other studies of women with a history of opioid use disorder (Krans et al, 2016; Liu et al, 2009). A recent study of 791 pregnant women with a history of opioid use disorder in Pittsburgh found that a lower proportion were tested (77%) but showed similar anti-HCV prevalence (60.4%) and even lower rates of RNA and genotype testing (Krans et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have found higher than expected HCV infection rates among pregnant women not involved in pharmacotherapy programs, including in Australia, England and the U.S. (Kuncio et al, 2015; Liu et al, 2009; Orkin, Jeffery-Smith, Foster, & Tong, 2016). This finding led proposals to adopt universal prenatal HCV screening, as was done in Australia and New Zealand (Wilson & Beckmann, 2015).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There were a number of contradictory findings raised by this survey. While the majority of clients had been tested for HCV, the reported HCV prevalence rate of 48% is significantly lower than previously reported . Generally, HCV exposure rates in high‐risk populations are approximately 80% .…”
Section: Discussionsupporting
confidence: 89%
“…Vertical transmission of HCV occurs in 5–10% of HCV viraemic mothers . In a recent study, we have shown that although more than 70% of mothers on a methadone program are HCV positive, less than 20% of their children are tested for HCV at 18 months of age . This suggests striking non‐adherence to current best practice, a lack of awareness of HCV in this high‐risk population and that many children in this high‐risk population are lost to follow‐up and thus not identified .…”
mentioning
confidence: 99%